Early postpartum luteal function after treatment with progestin and(or) gonadotropin-releasing hormone in dairy cattle - Mee, M.O.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2012)
Progestin (Norgestomet®) and(or) repeated low-dose infusions of GnRH (Cystorelin@) influenced the lifespan of the first corpus luteum after an induced ovulation. Holstein cows (n=32) were assigned at calving to four groups. Cows were treated with blank ear implants (days 2 to 9 after calving) and saline infusion (48 hr on days 10 arid II), progestin ear implants and saline infusion, blank implants and GnRH infusion, or progestin implants and GnRH infusion prior to a GnRH-induced ovulation (day 12). Four primiparous and four multiparous cows were assigned to each treatment. Fewer cows treated with progestin/GnRH ovulated in response to the GnRH challenge. However, short cycles (<17 days in duration) were prevented in all cows (n= 16) treated with progestin. In addition, all multiparous cows treated with blank implants and GnRH infusion had normal cycles. Results of this study suggested that progestin and GnRH may have altered follicular development, thereby preventing the short-lived corpus luteum and inducing a normal estrous cycle as cows overcame anestrus early postpartum.
Keywords: Dairy; Luteal function; Progestin; Gonadotropin-releasing hormone